Surprisingly fast assembly of the MOF film for synergetic antibacterial phototherapeutics. Issue 15 (15th July 2022) - Gao, Jie; Hao, Lingwan; Jiang, Rujian; Liu, Zhuo; Tian, Limei; Zhao, Jie; Ming, Weihua; Ren, Luquan
Abstract : A concept of developing a MOF film-based synergetic PTT/PDT antibacterial surface, through a sustainable and surprisingly fast chelation-induced self-assembly. Abstract : Antibacterial surfaces that provide synergetic photothermal/photodynamic therapy (PTT/PDT) offer a promising avenue for combating bacterial infections but generally require a time-consuming and cumbersome chemical preparation procedure. Herein, a metal–organic framework (MOF) composite film with PTT/PDT antibacterial performance is realized through a surprisingly fast and sustainable chelation-induced self-assembly between ZIF-8 particles and dopamine (DA). Unlike traditional DA polymerization, usually in an alkaline medium with a long reaction time ( e.g. more than 20 h), a robust and universal MOF composite film with DA as the linker can be rapidly assembled within only 0.5 h on various bulk materials under neutral (pH = 7) conditions. The resultant MOF film is extremely robust, and can even withstand harsh ultrasonic cleaning (150 W, 50 kHz, 10 min) and maintain its intact nanostructure. After being incorporated with indocyanine green (ICG), the obtained composite films achieved efficient synergetic PTT/PDT against both Gram-positive and -negative bacteria under single NIR irradiation (808 nm). This PTT/PDT antibacterial film also exhibited excellent in vitro biocompatibility, thus revealing the great potential for medical antibacterial surface applications.